The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jsams.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a platelet-rich plasma injection for the treatment of proximal hamstring tendinopathy: A pilot study

Abstract: Patients with PHT receiving a PRP injection did not improve on clinical outcomes at 8-weeks follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…This study indicates that the addition of PRP did not affect the improvement compared to administration of insulin without PRP. The results of the conclusions are the same as Levy et al (2018), who used PRP in patients who had problems with the tendon. But the results of this study are different from studies using PRP to repair damage to the ovaries and testes.…”
Section: Igf-1 Mrna Expression In Testicular Ratssupporting
confidence: 55%
“…This study indicates that the addition of PRP did not affect the improvement compared to administration of insulin without PRP. The results of the conclusions are the same as Levy et al (2018), who used PRP in patients who had problems with the tendon. But the results of this study are different from studies using PRP to repair damage to the ovaries and testes.…”
Section: Igf-1 Mrna Expression In Testicular Ratssupporting
confidence: 55%
“…There was no mention of post-PRP rehabilitation programs in several reported non-Achilles tendon PRP studies (e.g., common extensor tendinopathy) (186) (187). The lack of such programs could be of concern if physicians do not fully appreciate rehabilitation programs as an integral part of a clinical regenerative (tendon) treatment protocol, even though physical or occupational therapy is a commonly prescribed treatment option in patients suffering from tendinopathy.…”
Section: Combining Prp With Rehabilitationmentioning
confidence: 99%
“…Due to a small sample size, the authors of the study could not conclusively determine the efficacy of either whole blood injection or PRP for recalcitrant PHT. Levy et al 72 conducted a retrospective case series, including 29 patients with PHT with mild-to-severe tendinopathy who received one ultrasound-guided leukocyte-poor PRP injection. This study used a validated proximal hamstring-specific functional outcome measure, the Victorian Institute Sport Assessment-Proximal Hamstring Tendons (VISA-H) questionnaire.…”
Section: Prp For Proximal Hamstring Tendinopathymentioning
confidence: 99%
“…At 8-week follow-up, there was no significant improvement in VISA-H compared to baseline, and no significant difference in outcome across severity of tendinopathy. 72 A number of additional small case series have been published that suggest PRP may be useful for the management of PHT (Table 3). Fader et al 73 reported that 10 of 18 patients had 80% or greater improvement in pain scores (mean subjective improvement 63%) at 6 months after single PRP injection.…”
Section: Prp For Proximal Hamstring Tendinopathymentioning
confidence: 99%
See 1 more Smart Citation